The role of public relations campaigns in improving the image of the public institution: دراسة ميدانية بالمؤسسة الاستشفائية العمومية لولاية المدية - Ould Medjeber, Habib; Beloucif, Tayeb (Journal of Human Sciences, 2021)
This research is an attempt to deal with the issue of planning campaigns and public relations programs in the public hospital organization. It attempts shed the light on its various implementations in the different institutions of public hospitals of Medea state Moreover , it tries to demonstrate the role of these programs in improving the image of the institution and the reputation of their audiences.Moreover, the study also sheds the light on the reality of the practice of public relations in the offer- mentioned health institution its different activities among which planning for health and environmental messages with a social nature came at the forfront.Furthermore, this study is an attempt convey that  the number of activities carried in the health institution of Medea is guided by communication strategies. The latter , seek to achieve an understanding that common to both the institution its self and its audience. This is in the aim of improving the health institution reputation.